The Role of Female Activists in Enhancing Inter-Member Organizational Performance: A Case Study of the PMII Organization at UIN Sumatera Utara - Wulandari, Adetya Putri Arvia; Harahap, Aprilinda M. (Borong Newinera Publisher, 2025)
This study aims to examine the contributions of female activists to the performance of inter-member relations within the Indonesian Islamic Student Movement (PMII) organization at the State Islamic University of North Sumatra (UINSU). A qualitative research method was employed, with data collected through in-depth interviews involving rayon administrators from six faculties, as well as documentation and literature studies. The data were analyzed using qualitative descriptive analysis, consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that female activists play a significant role in fostering effective communication, resolving conflicts through persuasive approaches, and enhancing participation and solidarity among members. Their inclusive and empathetic leadership has been shown to create a conducive working environment and improve overall organizational effectiveness. The study concludes that the transformational leadership style exhibited by female activists contributes to the development of a collaborative, equitable, and gender-inclusive organizational culture.